DEMOCRATIC AND PARTICIPATORY SCHOOL MANAGEMENT: PATHWAYS TO BUILDING CITIZEN AND INCLUSIVE SCHOOLS (Editora Impacto Científico, 2026)
This study examines democratic and participatory school management as a fundamental axis for building inclusive and citizenship-oriented schools committed to the integral development of students. The research highlights that democratic management goes beyond administrative tasks, assuming pedagogical, political, and collective dimensions. Based on authors such as Libâneo, Lück, Paro and Gadotti, the study analyzes the principles of participation, autonomy, collegiality, and pedagogical leadership, emphasizing the crucial role of school principals as mediators and coordinators of collective work. It also discusses the importance of school councils, the collaborative development of the political-pedagogical project, and the strengthening of participatory culture to ensure transparency, shared responsibility, and social quality in education. The study concludes that democratic school management requires the articulation of legal frameworks, inclusive practices, community participation, and ongoing professional development, becoming an essential path for transforming the school into a space of citizenship, equity, and human development.DOI: https://doi.org/10.56238/edimpacto2025.090-093